2013
DOI: 10.1136/annrheumdis-2012-eular.299
|View full text |Cite
|
Sign up to set email alerts
|

AB0299 Quality of life in tunisian patients with rheumatoid arthritis: A cross-sectional study about 200 patients

Abstract: Background Rheumatoid arthritis (RA) is a chronic inflammatory disabling disease with significant impact on the quality of life (QOL) of patients. Health-related quality of life (HRQOL) issues are assuming increasing importance in chronic rheumatic diseases like RA. No data on QOL in RA is available from Tunisian patients. Objectives The aim of this study was to assess the HRQOL of Tunisian patients with RA and also to specify the influence of various parameters. Methods Consenting patients with rheumatoid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In the current study, it has been found that the median HAQ-DI score among RA patients was 0.94, while the scores from studies that used HAQ-DI in Egyptian patients were 1.08 [67] and 1.45 [68]. In Moroccan patients, the median HAQ-DI scores among RA patients were 1.40 [69], and 1.63 [23], while in Tunisian patients, the score was 1.7 [70].…”
Section: Discussionmentioning
confidence: 43%
“…In the current study, it has been found that the median HAQ-DI score among RA patients was 0.94, while the scores from studies that used HAQ-DI in Egyptian patients were 1.08 [67] and 1.45 [68]. In Moroccan patients, the median HAQ-DI scores among RA patients were 1.40 [69], and 1.63 [23], while in Tunisian patients, the score was 1.7 [70].…”
Section: Discussionmentioning
confidence: 43%